2011
DOI: 10.2174/1874467211104020115
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA Damage and Epigenetic DNA Methylation Changes in Radiation-Induced Genomic Instability and Bystander Effects in Germline In Vivo

Abstract: Ionizing radiation (IR) is a curative treatment for many human malignancies, an important diagnostic modality, and a pivotal preparative regimen for bone marrow transplantation. On the other hand, IR is a potent damaging agent that can affect a variety of processes in directly exposed cells, in their descendents, and in neighboring un-irradiated naïve 'bystander' cells. Accumulation of DNA damage caused by IR in conjunction with disrupted cellular regulation processes can lead to genome instability in the germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
0
18
0
1
Order By: Relevance
“…Further, the processing of closely spaced oxidative lesions (oxidatively-induced clustered clustered DNA lesions or OCDLs) can induce DNA double strand breaks, a serious type of DNA lesion that leads to cell death or long-term stressful effects in surviving cells [69; 70; 71]. Increasing evidence indicates that inflammatory cells in circulating blood of patients that received partial body irradiation may also induce DNA damage at sites that are distant from the irradiated target [4; 72], hence contributing to ‘out-of-field’or abscopal effects [5; 73; 74; 75]. Macrophages also secrete cytokines [76] that may perturb physiological functions in normal surrounding cells.…”
Section: Primary Effects Of Ionizing Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the processing of closely spaced oxidative lesions (oxidatively-induced clustered clustered DNA lesions or OCDLs) can induce DNA double strand breaks, a serious type of DNA lesion that leads to cell death or long-term stressful effects in surviving cells [69; 70; 71]. Increasing evidence indicates that inflammatory cells in circulating blood of patients that received partial body irradiation may also induce DNA damage at sites that are distant from the irradiated target [4; 72], hence contributing to ‘out-of-field’or abscopal effects [5; 73; 74; 75]. Macrophages also secrete cytokines [76] that may perturb physiological functions in normal surrounding cells.…”
Section: Primary Effects Of Ionizing Radiationmentioning
confidence: 99%
“…Hence, the effects of localized energy deposition events in a cell may not be assessed independently of neighboring cells. Whereas, certain genetic and epigenetic changes in targeted and non-targeted cells may be observed shortly after exposure [5; 6; 54; 77], others require several generations to be expressed [10; 78; 79; 80]. Certain effects (e.g.…”
Section: Primary Effects Of Ionizing Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial theories to explain genomic instability within the existing framework centered around ideas that a mutator phenotype had been activated (Loeb, 2011) but the very high yields of non-clonal genetic damage inducible even by culture medium from irradiated cells made this unlikely as did the persistent nature of the effect which was neither selected out nor ultimately dominant (Seymour and Mothersill, 1988, 1997; Mendonca et al, 1989). It has been suggested that an external epigenetic driver is involved such as oxy-radicals (Hamada et al, 2011), methylation changes (Kaup et al, 2006; Tamminga and Kovalchuk, 2011), or miRNA mediated signaling (Ilnytskyy et al, 2009; Kovalchuk et al, 2010) but because a single exposure to radiation can turn on the process indefinitely both in vitro and in vivo (O’Reilly et al, 1994; Mothersill et al, 2000, 2010) this hypothesis requires the driver to be permanently activated both in time and in space following a single exposure to ultra-low doses of radiation. An important conceptual point here is that signal generation and response to the signal are separate processes and may not both occur in a single system (Vines et al, 2008).…”
Section: Challenges To Conventional Genetics Posed By Non-targeted Efmentioning
confidence: 99%
“…Importantly, space flight-induced effects on the immune system (204) and the ensuing inflammation and perturbations in oxidative metabolism (91,156,237) increase the risk of cancer (237,295). When macrophages and neutrophils are recruited to sites of inflammation, they generate ROS and RNS, which can cause a large spectrum of oxidative damage in neighboring cells (48,75), hence contributing to out-of-field or abscopal effects (142,192,212,269). Interestingly, low doses/low fluences of protons and HZE particles have been shown to trigger numerical and phenotypic changes in immune/inflammatory cells (112)(113)(114)259) and changes in cytokine levels (236,246) in mice.…”
mentioning
confidence: 99%